Questions of studying the effectiveness of online education in the design field in various commercial platforms - Sadykova Жанна; Kanafina Сауле (Рroblems of engineering and professional education, 2022)
The article analyzes the state of the education system of Kazakhstan. The ways of developing the means of creative profession as a design are considered. A comparative analysis of the quality of knowledge obtained between universities and distance education platforms is carried out, during which the potential of online courses as an effective teaching method is determined.